2017
DOI: 10.1002/mp.12350
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive Fuzzy C-means method utilizing neighboring information for breast tumor segmentation in ultrasound images

Abstract: Inclusion of the pixel neighbor information adaptively in segmenting US images improved the segmentation performance. The results demonstrate the potential application of the method in breast tumor CAD and other US-guided procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Apparently, all global thresholding methods can be applied in the accumulating process. It was testified that the level set and the FCM could be used in the local window to achieve better results when compared with the traditional ones [34]. Thus, they can be applied in the accumulating process.…”
Section: Multi‐methods Combination Frameworkmentioning
confidence: 99%
“…Apparently, all global thresholding methods can be applied in the accumulating process. It was testified that the level set and the FCM could be used in the local window to achieve better results when compared with the traditional ones [34]. Thus, they can be applied in the accumulating process.…”
Section: Multi‐methods Combination Frameworkmentioning
confidence: 99%
“…For region-based segmentation, both traditional methods and machine-learning-based pixel classification methods were investigated. Feng et al [17] adopted an adaptive fuzzy C-means algorithm and the obtained DSC is 0.925. Pons et al [18] reported that their evaluated automated method achieved a DSC of 0.49 using a Markov Random Field (MRF) and a Maximum a Posteriori (MAP) approach, by applying it to clinical data.…”
Section: Fig 1 a Malignant Lesion In Breast Ultrasoundmentioning
confidence: 99%
“…Recently, great progress has been made in processing and segmentation of images and selection of regions of interest (ROIs) in CAD. Feng et al[14] proposed a method of adaptively utilizing neighboring information, which can effectively improve the breast tumor segmentation performance on ultrasound images. Cai et al[15] proposed a phased congruency-based binary pattern texture descriptor, which is effective and robust to segament and classify B-mode ultrasound images regardless of image grey-scale variation.…”
Section: Segmentationmentioning
confidence: 99%